Effects of Voice and Biographic Data on Face Encoding - Thilda Karlsson; Heidi Schaefer; Jason J. S. Barton; Sherryse L. Corrow (Brain Sciences, 2023)
There are various perceptual and informational cues for recognizing people. How these interact in the recognition process is of interest. Our goal was to determine if the encoding of faces was enhanced by the concurrent presence of a voice, biographic data, or both. Using a between-subject design, four groups of 10 subjects learned the identities of 24 faces seen in video-clips. Half of the faces were seen only with their names, while the other half had additional information. For the first group this was the person’s voice, for the second, it was biographic data, and for the third, both voice and biographic data. In a fourth control group, the additional information was the voice of a generic narrator relating non-biographic information. In the retrieval phase, subjects performed a familiarity task and then a face-to-name identification task with dynamic faces alone. Our results consistently showed no benefit to face encoding with additional information, for either the familiarity or identification task. Tests for equivalency indicated that facilitative effects of a voice or biographic data on face encoding were not likely to exceed 3% in accuracy. We conclude that face encoding is minimally influenced by cross-modal information from voices or biographic data.